Detection of inducible clindamycin resistance in methicillin-resistant and -susceptible staphylococcus aureus isolated from clinical samples in a tertiary care hospital of Dhaka City - Parvin, Syeda Adeeba (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology, 2024.